2015
DOI: 10.3389/fpls.2015.00125
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the link between salicylic acid signaling and sphingolipid metabolism

Abstract: The field of plant sphingolipid biology has evolved in recent years. Sphingolipids are abundant in cell membranes, and genetic analyses revealed essential roles for these lipids in plant growth, development, and responses to abiotic and biotic stress. Salicylic acid (SA) is a key signaling molecule that is required for induction of defense-related genes and rapid and localized cell death at the site of pathogen infection (hypersensitive response) during incompatible host–pathogen interactions. Conceivably, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 53 publications
1
36
0
Order By: Relevance
“…Collectively, our results suggested that AtDPL1 could be a negative and/or a positive regulator of the JA-and SA-regulated defense pathway, respectively. Whereas a relationship between SA signaling and sphingolipids has often been described (Sánchez-Rangel et al, 2015), our results highlight, to our knowledge for the first time, that sphingolipids could also play a key role in the JA signaling pathway.…”
Section: Interconnections Between Sphingolipids and Defense Mechanismssupporting
confidence: 58%
See 1 more Smart Citation
“…Collectively, our results suggested that AtDPL1 could be a negative and/or a positive regulator of the JA-and SA-regulated defense pathway, respectively. Whereas a relationship between SA signaling and sphingolipids has often been described (Sánchez-Rangel et al, 2015), our results highlight, to our knowledge for the first time, that sphingolipids could also play a key role in the JA signaling pathway.…”
Section: Interconnections Between Sphingolipids and Defense Mechanismssupporting
confidence: 58%
“…Recently, it was shown that SA and its analog benzothiadiazole affect sphingolipid metabolism (Shi et al, 2015), including AtDPL1 gene expression (Wang et al, 2006). Since activation of the SA-dependent pathway is effective against biotrophic and hemibiotrophic pathogens, it has been postulated that sphingolipids played a key role in defense against such pathogens in an SA-dependent pathway (Sánchez-Rangel et al, 2015). However, whereas acd5, erh1, and the double mutant fah1/fah2 exhibited enhanced resistance to powdery mildew, they displayed a similar phenotype to wild-type plants upon infection with P. syringae pv maculicola or Verticillium longisporum (Wang et al, 2008;König et al, 2012).…”
Section: Interconnections Between Sphingolipids and Defense Mechanismsmentioning
confidence: 99%
“…Likewise, a previous study revealed that BPH14 gene confers rice resistance to BPH (Du et al, 2009) and cotton photosynthesis-related gene ( GhPSAK1 ) enhanced SA signaling pathway in transgenic plants (Zhang et al, 2014). Sánchez-Rangel et al (2015) reviewed that sphingolipid played a key role in defense against pathogen in SA-dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, how MI accumulation modulates SA biosynthesis and this only in LD conditions remains unknown. An interesting research axis concerns the alteration of ceramides homeostasis since relative accumulation of ceramides and their derivatives appear as key elements for the control of plant PCD via SA-signaling pathway (Sánchez-Rangel et al, 2015). Donahue et al (2010) reported elevated levels of ceramides and of hydroxyceramides in mips1, correlated with the decline of MI and of its derivative phosphatidylinositol.…”
Section: Discussionmentioning
confidence: 99%